Lecturer Internship Program to Develop Classroom Management Strategies for Digi-X Program at Liputan6.com - Fatma Hetami; Mohamad Ikhwan Rosyidi; Thohiriyah Thohiriyah; Izzati Gemi Seinsiani; Sri Sumaryani (Universitas Negeri Semarang, 2022)
A digital content education program established by Liputan 6.com under the name of Digi-X was created to fill out the demand of digital education by the public. Digi-X has been frequently invited to open classes and give talks on how to develop the company profiling and to share information in a more effective and engaging way to public and private sectors. The workshops have various presenters and the materials are delivered in a lecture-like format. Through an internship program between Liputan 6.com and the English Literature Study Program of UNNES that has begun since 2021, four lecturers-cum-researchers are invited to review the Digi-X performance. Based on the interview, survey and observation of the Digi-X documents, materials, and classes, Digi-X needs to improve the quality of its course documents, particularly the lesson plans. We argue that by arranging them in a detailed and engaging format, they can guide the speakers in terms of material coverage, learning goals and time management. In exchange, the internship program equips the lecturers with real-life knowledge and skills on management and types of works in the journalism industry that can be inserted in the lesson plans and implemented in class.